Study of noise reduction methods in the sound sequence when solving the speech-to-textproblem - Barkovska, Olesia; Kholiev, Vladyslav; Lytvynenko, Vladyslav (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject of this research is noise reduction methods in the sound sequence as a part of the proposed speech-to-text (STT) module for converting a verbal lecture or a lesson into a written text form ondigital educational platforms.The goalis to investigate the influence of noise reduction methods on the operation of the acoustic signal recognition system. 3 methodsof noise reduction were considered for integration in the proposed acoustic artifact recognition system and for the researching: spectral subtraction method; fast Fourier transform; Wiener filter withsoftware modelingof every method. The obtained results: after testing the system with integrated noise reduction modules in it, based on the fast Fourier transform, Wiener filter and spectral subtraction method, it was concluded that the module using the Wiener filter improves the identification results by 25%, which is the highest result. However, performance testing has shownthat fast Fourier transform is the fastest method.The practical significanceof the work is –the identifying acoustic events system was developed, different noise reduction methods were integrated and researched into the module for converting a verbal lecture or a lesson into a written text form in a proposed system with the aim of increasing of speed and accuracy.

Предметом дослідження є методи шумоподавлення у звуковій послідовності у складі пропонованого модуля перетворення мови в текст (STT) для представлення усної лекції або уроку в текстовому вигляді на цифрових освітніх платформах. Мета – дослідити вплив методів шумозаглушення на роботу системи розпізнавання акустичного сигналу. Для інтеграції в запропоновану систему розпізнавання акустичних артефактів та для дослідження було розглянуто три методизменшення шуму: метод спектрального віднімання; швидке перетворення Фур'є; Фільтр Вінера з програмним моделюванням кожного методу. Отримані результати: після тестування системи з інтегрованими в неї модулями шумозаглушення на основі швидкого перетворення Фур'є, фільтра Вінера та методу спектрального віднімання було зроблено висновок, що модуль із застосуванням фільтра Вінера покращує результати ідентифікаціїакустичних артефактівна 25%, що є найвищий результат. Проте тестування продуктивності показало, що швидке перетворення Фур'є найшвидшим методом. Практична значущість роботиполягає в тому, що запропоновано та зробленомодулісистемиідентифікації акустичних подій, інтегровано та досліджено різні методи шумозаглушення в модуль для перетворення усної лекції чи уроку в письмову текстову форму в запропонованій системі з метою збільшення швидкостіі точності результату.
Вивчення методів зниження шуму в звуковому ряді для вирішення задач перетворення мови в текст
Keywords: speech; voice; processingu; noise; reduction; filtering; learning management systems; digital educational platform; мовлення; голос; обробка; шум; скорочення; фільтрація; системи управління навчанням; цифрова освітня платформа